NLOS location enhancement algorithm based on depth-first multipath parameter estimation - Xiaofeng LU; Ye DONG; Yuejie LI (Tongxin xuebao)
In order to improve the positioning accuracy of millimeter wave system with non-line-of-sight (NLOS) paths, a depth-first multipath parameter estimation algorithm was proposed based on distributed compressed sensing.According to the evaluated multipath parameters, NLOS path could be identified, so that the localization performance was enhanced.Firstly, depth-first algorithm was applied to reduce the unnecessary path searching, and the more accurate multipath parameters were obtained.Secondly, under the reverse positioning distance residual method, NLOS path recognition could be carried out.Then, the scatterers in the NLOS path were matched, and the position of which were regarded as virtual anchor nodes.Combining the information of base stations and virtual anchor nodes, positioning enhancement was realized.Finally, localization performance of the proposed algorithm was simulated, compared with the distance weighted least square (LS) and maximum discrimination transformation (MDT) algorithms, the performance of the proposed algorithm is improved by 17% and 8% respectively.